Monitoring the swimmer`s training load: a narrative review of monitoring strategies applied in research - Feijen, S.; Tate, A.; Kuppens, K.; Barry, L. A.; Struyf, F. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The high incidence of injury during swim-training as well as the increasing demands of the sports make monitoring of the swimmer`s training load a key concept requiring further investigation. Research has previously introduced numerous methods for the purposes of monitoring the swimmer`s training load, but a narrative review discussing the strengths and limitations of each method is lacking. Consequently, this narrative review aims to summarize the monitoring strategies that have been applied in sports medicine research on competitive swimmers. This knowledge can assist professionals in the field in choosing which method is appropriate in their particular setting. The results from this study showed that external training load was predominantly obtained through real-life observation of the swimmers` training volume. However, research has investigated a number of internal load monitoring tools, including blood lactate, training heart rate and perceived effort of training. To date, blood lactate markers are still considered most accurate and especially recommended at higher levels of competitive swimming or for those at greater risk of injury. Further, mood state profiling has been suggested as an early indicator of overtraining and may be applied at the lower competitive levels of swimming. Professionals in the field should consider the individual, the aim of the current training phase and additional logistical issues when determining the appropriate monitoring strategy in their setting.